Photoresponse water photovoltaic power generation device based on nano tungsten oxide and preparation method of photoresponse water photovoltaic power generation device

By using a light-responsive material based on tungsten oxide in hydrovoltaic power generation devices, the photoconductivity and hydrovoltaic power generation materials are coupled, and the problem of low output power of existing hydrovoltaic power generation materials is solved, thereby realizing the regulation of voltage and current under light and efficient power output.

CN119582646APending Publication Date: 2025-03-07NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202411626697.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The output power of existing hydrovoltaic power generation materials is low, limiting the commercial application of hydrovoltaic power generation devices.

Method used

Using a photoresponsive material based on tungsten oxide to couple the photoconductivity with hydrovoltaics, a hydrovoltaic power generation device that can regulate voltage and current under light was developed.

Benefits of technology

The voltage and current regulation under the action of light is achieved, and excellent power output and voltage stability are obtained, with a duration of up to more than 72 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119582646A_ABST
    Figure CN119582646A_ABST
Patent Text Reader

Abstract

The invention provides a photoresponse water photovoltaic power generation device based on nano tungsten oxide and a preparation method of the photoresponse water photovoltaic power generation device, and relates to the field of water evaporation induced new energy power generation and novel photoelectric detection. The water photovoltaic power generation device is composed of a substrate, a positive electrode, a negative electrode and a slurry layer, wherein the slurry layer is obtained by drying slurry formed by mixing tungsten oxide, a Nafion solution and deionized water; the water photovoltaic power generation device can generate an open-circuit voltage of 1.4-1.8 V and a short-circuit current of 100-140 nA under the evaporation induction of deionized water. Under the illumination with the wavelength of 435 nm, the output voltage and current change along with the illumination intensity, and the material has the obvious light response characteristic and is expected to be used for optical detection and hydrovolt generator theory research.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of hydrovoltaic power generation, in particular to a hydrovoltaic evaporation power generation device based on tungsten oxide light response material. Background Art

[0002] The hydrovoltaic effect is an emerging technology that generates electricity through direct interaction between materials and various forms of water (such as raindrops, waves, rivers, etc.). Hydrovoltaic power generation refers to an emerging technology that uses the potential energy in various forms of water in the environment to obtain electricity. Its principle is based on the ion flow induced by the movement of the double electric layer boundary at the interface between water and materials, which causes the carriers in the conductor to move in a directional manner, thereby converting water energy into electrical energy. After several years of development, hydrovoltaic technology covers a wide range of material systems, mainly nanocarbon materials, but the output power of hydrovoltaic materials reported so far is relatively low, which also seriously restricts the commercial application of hydrovoltaic power generation devices.

[0003] The study of non-equilibrium carriers shows that light absorption causes non-equilibrium carriers to form in semiconductors, and the increase in carrier concentration will inevitably increase the conductivity. This phenomenon of increased semiconductor conductivity caused by light is called photoconductivity. Because the resistance of a hydrovoltaic device has a significant effect on the voltage and current, the phenomenon of photoinduced conductivity change has broad application prospects in the cross-field of hydrovoltaic evaporation power generation technology.

[0004] Tungsten oxide is a cleaning material commonly used for photocatalytic decomposition after titanium dioxide, because tungsten oxide has good absorption capacity for blue and violet light, and it has electrochromic properties, so it is used in new energy fields such as photocatalysis and batteries. At present, there are no reports on the preparation of hydrovoltaic power generation devices based on the light response characteristics of tungsten oxide. Summary of the invention

[0005] In view of the above problems, the present application provides a light-responsive hydrovoltaic power generation device based on tungsten oxide material, which couples photoconductivity with hydrovoltaics to achieve light-responsive hydrovoltaic power generation. The voltage and current generated by the device will change with light of a certain wavelength, thereby achieving light-regulated hydrovoltaic evaporation power generation output and obtaining excellent power output and voltage.

[0006] To achieve the above purpose, the technical solution adopted by the embodiment of the present invention is:

[0007] First, the present application provides a photoresponsive hydrovoltaic power generation device based on nano tungsten oxide, which includes a substrate, a positive electrode, a negative electrode and a slurry layer on the surface of the substrate; the slurry layer is located between the positive electrode and the negative electrode and covers part of the positive electrode and part of the negative electrode; the above-mentioned slurry layer is obtained by drying a slurry formed by mixing tungsten oxide (WO3), Nafion solution and deionized water at 600°C.

[0008] Preferably, the substrate material includes ceramic and quartz; and the electrode material is gold.

[0009] Preferably, in the above slurry solution, the mass volume ratio of tungsten oxide to Nafion solution is 20:9, the unit of mass volume ratio is mg / ul, and the volume ratio of Nafion solution to deionized water is 9:91.

[0010] Secondly, the present application provides a method for preparing the above-mentioned light-responsive hydrovoltaic power generation device, the specific steps of which include:

[0011] S01, using a magnetic stirrer and an ultrasonic cleaner, uniformly mix the tungsten oxide nanoparticle powder, the Nafion solution and the deionized water to prepare a slurry for coating, and set aside;

[0012] S02, prepare an electrode template, the hollowed-out portion of the electrode template is the target electrode shape, then attach the template to the substrate surface, use a metal sputtering device to sputter metal on the substrate surface, and the hollowed-out portion of the template forms the positive electrode and negative electrode of the power generation device; the sputtered metal material is preferably gold, which is resistant to high temperatures and stable. In the embodiment of the present application, the distance between the positive electrode and the negative electrode is 1.5 cm, the electrode length is 2 cm, and the width is 2 mm.

[0013] S03, applying the slurry on the substrate surface between the positive electrode and the negative electrode and covering part of the positive electrode and the negative electrode, and then heating and drying on a hot stage at 90° C. to form a porous film;

[0014] S04, put it into a muffle furnace and heat it at 600℃ for 1 hour to decompose the Nafion inside at high temperature, take it out after natural cooling, soak it in deionized water for 5 hours (to stabilize its pore structure), then take it out and dry it to obtain a photoresponsive hydrovoltaic power generation device.

[0015] Preferably, the uniform mixing in step S01 means: first, the three raw materials are stirred for 20 minutes using a magnetic stirrer at a speed of 600 r / min; then, they are placed in an ultrasonic cleaning machine using a power of 80 W and a frequency of 40 KHz for 20 minutes for further oscillation dispersion; finally, they are placed in a magnetic stirrer for stirring for 6 hours at a speed of 600 r / min.

[0016] As a preferred embodiment, when mixing the slurry in step S01, first weigh the tungsten oxide powder and pour it into a glass bottle, then add deionized water, and finally add the Nafion solution.

[0017] Preferably, the sputtering time in step S02 is 30 minutes. If the sputtering time is too short, the gold electrode will lose its conductivity when heated at high temperature. Before sputtering, an acrylic plate is cut into the shape of the electrode template on a laser cutting machine, and then covered on the ceramic substrate and bonded with tape.

[0018] Preferably, the smearing concentration in step S03 is preferably 40ul / cm 2 , after the concentration is applied, there will be no cracking or unevenness. In the embodiment of the present application, the application length of the slurry along the positive and negative electrode directions is 1.5 cm, so as to match the capillary height limit during hydrovoltaic power generation and improve the power generation effect.

[0019] Preferably, the heating procedure of step S04 is: uniformly heating from room temperature (about 20°C) to 600°C (heating rate is 19.3°C / min) for 30 minutes, and then maintaining heating at 600°C for 1 hour. After heating, wait for it to slowly cool naturally in the muffle furnace, and take it out when the temperature is lower than 100°C (preferably cooled to room temperature).

[0020] Compared with the traditional water evaporation induced power generation, this application couples light and water evaporation induced power generation, which can achieve that the voltage and current can respond to light while evaporation generates electricity. It not only has good voltage and current performance, but also has an additional light-responsive characteristic. It realizes the regulation of voltage and current under the action of light. Specifically, this application has the following beneficial effects:

[0021] 1. The method for preparing the material is simple, the raw materials are easy to obtain, and the preparation cycle is short.

[0022] 2. The generated voltage is stable and lasts for a long time, and the voltage can last for more than 72 hours.

[0023] 3. During the hydrovoltaic power generation process, when the material is irradiated with light waves with a wavelength of 300nm to 500nm, the voltage will decrease and the current will increase. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of the preparation process of tungsten oxide devices.

[0025] Figure 2 These are the actual pictures of the electrode sputtering template and the actual pictures of the template placed on the substrate after sputtering.

[0026] Figure 3 This is a schematic diagram of the device structure prepared in Example 1;

[0027] Among them, 1-electrode negative electrode, 2-electrode positive electrode, 3-substrate, 4-slurry layer.

[0028] Figure 4 This is a photo of the hydrovoltaic evaporation device prepared in Example 1.

[0029] Figure 5This is a schematic diagram of the test of the hydroevaporation device (with alumina ceramic as the substrate) prepared in Example 1 under the irradiation of light with a wavelength of 300nm to 500nm.

[0030] Figure 6 The voltage obtained by the hydrovoltaic evaporation device (using alumina ceramic as the substrate) prepared in Example 1 in deionized water.

[0031] Figure 7 The current size of the hydrovoltaic evaporation device (with alumina ceramic as the substrate) prepared in Example 1 measured in deionized water.

[0032] Figure 8 The voltage change of the hydrovoltaic evaporation device (with alumina ceramic as the substrate) prepared in Example 1 when irradiated with 430nm blue light in deionized water (the voltage drops when illuminated, and rises again when the light is removed). Fig. 9 This is the current change of the hydrovoltaic evaporation device (with alumina ceramic as the substrate) prepared in Example 1 when irradiated with 430nm blue light in deionized water. (The current rises when the light is irradiated, and then falls back when the light is removed). DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below. Embodiments of the present invention will be described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention.

[0034] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in common dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless defined as herein.

[0035] The method provided by the embodiment of the present invention can easily adhere a 150um thick tungsten trioxide material film on the surface of the substrate. The tungsten trioxide film has good rigidity and is not easy to fall off on the surface of the substrate. It can generate electricity without being damaged in high humidity, low humidity, and high temperature environments. The voltage and current collection is relatively stable, easy to prepare, and has the potential for large-scale industrial production.

[0036] Sources of raw materials involved in the embodiments:

[0037] The alumina ceramic sheet was purchased from Guangzhou Yunyi Electronics Co., Ltd. It is a conventional ceramic sheet containing 96% alumina and is white in color. The thermal conductivity is 29.3W / mK. The insulation voltage is below 22.5kV and the temperature resistance is up to 1600℃.

[0038] Nano-tungsten trioxide powder was purchased from Aladdin (www.aladdin-e.com), with a particle size of <200 nm, 99.9% metals basis, and a CAS number of 1314-35-8.

[0039] Deionized water: prepared using a commercially available filtration machine (UNIQUE-R20 pure water machine), using a circulating filtration method to remove particles from tap water, with a resistivity of 18.25 MΩ·cm.

[0040] Nafion (D520) solution was purchased from Materials Science Station (wwwScimaterials.cn), and its parameters are shown in Table 1 below. It is a conventional commercially available Nafion solution.

[0041] Table 1 Nafion D520 parameters

[0042]

[0043]

[0044] The ultrasonic cleaning machine was purchased from Yumeng, model number is YM-008.

[0045] The laser engraving machine was purchased from Foster, model FST-4060.

[0046] The dust-free paper was purchased from Enlai Poetry.

[0047] The high vacuum ion sputtering instrument was purchased from Quorum, model 150T Plus.

[0048] The electronic analytical balance was purchased from LICHEN / Lichen, model FA2004.

[0049] The heating stage was purchased from OHAUS, model number is e-G31HS07C.

[0050] The muffle furnace was purchased from Kehao, model KSL-1100C-S.

[0051] Example 1 Preparation of a hydrovoltaic power generation device based on an alumina ceramic sheet

[0052] The preparation process of the hydrovoltaic power generation device in this embodiment is as follows: Figure 1 As shown, the specific steps are as follows:

[0053] 1) Select an alumina ceramic sheet as the substrate, use an ultrasonic cleaner at a mid-band frequency of 40KHz to clean the surface of the alumina ceramic for 10 minutes, then wipe it clean with dust-free paper and set aside.

[0054] 2) Use RD works software to draw the target template shape on the computer, and then use a laser engraving machine to engrave the template shape (the hollowed-out part of the template is the target electrode shape). The template material is a 3mm thick acrylic plastic plate, the laser power is 50W, the maximum power is 80%, and the speed is 20mm / s. The actual template is as follows Figure 2 As shown in A.

[0055] 3) The engraved template is taped to the cleaned alumina ceramic substrate in step 1), and then the alumina ceramic sheet is placed in the sputtering chamber using a high vacuum ion sputtering instrument. Gold (Au) is selected as the metal target. -3 Under the condition of mbar, the sputtering current is 20mA, the sputtering time is 1800s, and the sample after sputtering is as follows Figure 2 As shown in B, the template is sputtered on the unmasked area of ​​the substrate to form a target electrode (Au), and then the template is removed to obtain a substrate containing an electrode for use.

[0056] 5) Weigh 400 mg of nano-tungsten trioxide powder using an electronic analytical balance and pour it into a brown light-proof glass bottle (volume 10 ml, height 51 mm, bottom diameter 22 mm). Then add 1820 ul (microliter) of deionized water and 180 ul of Nafion (D520) solution and polytetrafluoroethylene magnet (length 10 mm, width 4 mm, ellipsoidal shape) in sequence, and finally put it on a magnetic stirrer and stir it at a speed of 600 r / min for 20 minutes, then put it into an ultrasonic cleaner for further oscillation and dispersion, use 80 W power, 40 KHz frequency ultrasound for 20 minutes, then put it into a magnetic stirrer and stir it at 600 rpm for 6 hours to obtain a slurry for standby use.

[0057] 6) Preheat the heating table to 90°C, place the substrate containing the electrodes, and apply the slurry on the surface of the substrate and between the positive and negative electrodes. One end of the slurry covers part of the positive electrode and the other end covers part of the negative electrode. In this embodiment, the slurry coating area is a rectangle with a length of 2 cm and a width of 1.5 cm, and the coating amount is 120ul. After coating, place the sample on the hot table and wait for it to dry and solidify.

[0058] 7) Place the prepared sample in a muffle furnace, set the heating program to heat at 20°C for 30 minutes to 600°C (heating rate of 19.3°C / min), maintain the furnace temperature at 600°C for 1 hour, then stop heating and wait for it to cool naturally to room temperature, about 2 to 3 hours.

[0059] 8) Soak the heated sample in deionized water for 5 hours, take it out, and dry it naturally to obtain the final hydrovoltaic power generation device. The structural diagram is shown in Figure 3 As shown, the actual photos are as Figure 4 shown.

[0060] The performance of the power generation device was tested by connecting the positive and negative electrodes of the hydrovoltaic power generation device to a multimeter and testing it under 300nm to 500nm wavelength light. The test diagram is shown in the figure below. Figure 5 As shown in the figure, the red line is the positive pole and the black line is the negative pole.

[0061] The hydrovoltaic power generation device was placed in a container filled with deionized water at an angle, with the bottom of the device immersed in the deionized water (the water just covered the lower end of the negative electrode). The positive and negative electrodes were connected to a digital multimeter (Keithley DMM6500) to detect the voltage of the hydrovoltaic power generation device. The test results are as follows: Figure 6 As shown, the current detection results are as follows Figure 7 shown.

[0062] Use LED lamp beads, perpendicular to the surface of the ceramic sheet at a distance of 5 cm, and illuminate the power generation device with 430nm blue light. The voltage changes as follows Figure 8 As shown, the current changes as Fig. 9 As shown in the figure, it can be seen that the normal voltage is about 1.8V. When it is illuminated, the voltage drops to about 0.5V. When the light is removed, the voltage rises and recovers. When the current is illuminated, it rises from the original 100nA to 160nA. When the light is removed, the current drops and recovers.

[0063] Example 2

[0064] 1) In this embodiment, a frosted quartz sheet (purchased from Lianyungang Bobang Quartz Products Co., Ltd., with a size of 3cm*3cm and a thickness of 1mm) is selected as the substrate. The frosted quartz sheet has a light transmittance of >90%, a smoothness of 60 / 40, and can withstand a high temperature of 1200°C. It is a conventional quartz sheet.

[0065] 2) Ultrasonic cleaning (40KHz) of the frosted quartz surface for 10 minutes, and then placing it on a hot stage to dry the surface moisture.

[0066] 3) Use RD works software to draw the target template shape on the computer, and then use a laser engraving machine to engrave the template shape (the hollowed-out part of the template is the target electrode shape). The template material is an acrylic plastic plate with a thickness of 3 mm, the laser power is 50 W, the maximum power is selected to be 80%, and the speed is 20 mm / s.

[0067] 4) The cut template is attached to the cleaned frosted quartz substrate with tape, and then the frosted quartz substrate is placed in a high vacuum ion sputtering chamber, and gold (Au) is selected as the metal target. Under the condition of a vacuum degree of 10-3 mbar, the sputtering current is 20 mA, and the sputtering time is 1800 s.

[0068] 5) Weigh 400 mg of nano-tungsten trioxide powder and pour it into a brown light-proof glass bottle. Then add 1820 ul of deionized water and 180 ul of Nafion (D520) solution and polytetrafluoroethylene magnets, and finally put it on a magnetic stirrer and stir it at a speed of 600 r / min for 20 minutes, then put it into an ultrasonic cleaner for further vibration and dispersion, and then put it into a magnetic stirrer for stirring for 6 hours after ultrasonication for 20 minutes to obtain a slurry;

[0069] 6) Preheat the heating table to 90°C. Apply the prepared slurry solution in the middle of the sputtered electrode shape. The area of ​​the coating area is 2 cm long and 1.5 cm high. The coating amount is 120 ul. Apply the solution evenly on the frosted quartz substrate and place it on the hot table to wait for it to dry and solidify.

[0070] 7) Place the finished sample in a muffle furnace, set the heating program to heat from 20°C to 600°C for 10 minutes, maintain the furnace temperature at 600°C for 1 hour, then stop heating and wait for it to cool to room temperature, about 2 to 3 hours.

[0071] 8) Soak the heated sample in deionized water for 5 hours and then take it out to obtain the final product.

Claims

1. A photoresponsive hydrovoltaic power generation device based on nano-tungsten oxide, characterized in that: The device includes a substrate, a positive electrode, a negative electrode and a slurry layer are arranged on the surface of the substrate, the slurry layer is arranged between the positive electrode and the negative electrode, and the slurry layer covers part of the positive electrode and the negative electrode; the slurry layer is obtained by drying a slurry formed by mixing tungsten oxide, Nafion solution and deionized water.

2. The light-responsive hydrovoltaic power generation device based on nano-tungsten oxide according to claim 1, characterized in that: The substrate is made of ceramic or quartz.

3. The light-responsive hydrovoltaic power generation device based on nano-tungsten oxide according to claim 1, characterized in that: The positive electrode and the negative electrode are made of gold.

4. The light-responsive hydrovoltaic power generation device based on nano-tungsten oxide according to claim 1, characterized in that: In the slurry, the mass volume ratio of tungsten oxide to Nafion solution is 20:9, and the unit of mass volume ratio is mg / ul; the volume ratio of Nafion solution to deionized water is 9:

91.

5. The method for preparing a light-responsive hydrovoltaic power generation device based on nano-tungsten oxide according to any one of claims 1 to 4, characterized in that: The specific steps are as follows: 1) Mix tungsten oxide, Nafion solution and deionized water evenly to make slurry for later use; 2) Prepare an electrode template and attach it to the substrate surface; sputter metal on the substrate surface, and the hollowed-out portion of the template forms a positive electrode and a negative electrode on the substrate surface; 3) Applying the slurry on the substrate surface between the positive electrode and the negative electrode and covering part of the positive electrode and the negative electrode, placing the slurry in a muffle furnace after drying, heating it at 600° C. for 1 hour, cooling it, soaking it in deionized water, and then taking it out and drying it, thereby obtaining the photoresponsive hydrovoltaic power generation device based on nano-tungsten oxide.

6. The method for preparing a light-responsive hydrovoltaic power generation device based on nano-tungsten oxide according to claim 5, characterized in that: Step 2) The sputtering time is 30 minutes.

7. The method for preparing a light-responsive hydrovoltaic power generation device based on nano-tungsten oxide according to claim 5, characterized in that: Step 3) The smearing means that the slurry is applied at a concentration of 40ul / cm 2 .

8. The method for preparing a light-responsive hydrovoltaic power generation device based on nano-tungsten oxide according to claim 5, characterized in that: Step 3) the heating at 600° C. for 1 hour means firstly heating from room temperature to 600° C. at a uniform rate over 30 minutes, and then maintaining heating at 600° C. for 1 hour.

Citation Information

Patent Citations

  • Preparation method of functional area of nano aluminum-based watervoltaic and seawater desalination device

    CN111204830A

  • High-efficiency silicon-based photovoltaic device and preparation method thereof

    CN115765522A

  • Photo-thermal-hydraulic synergistic effect wide-spectrum plasmon core-shell material and device preparation method

    CN116586608A

  • Novel coastal zone repairing method

    CN116947171A

  • Perovskite oxide and application thereof in water vapor power generation

    CN118458831A

Cited By

  • Ultraviolet photoelectric sensor based on surface ion transport and preparation method and application thereof

    CN121207322A

  • Carbon nano hollow sphere water photovoltaic power generation device with partition resistors and preparation method thereof

    CN121546945A